Effectiveness of Using the Calendar Method of Self-Monitoring Medication Side Effects in SLE Patients - Yuwindry, Iwan; Yusri; Tangkas, Hansel Hens (International Journal of Clinical Inventions and Medical Sciences (IJCIMS), 2024)
An autoimmune rheumatic disease that produces widespread inflammation, affecting organs or systems in the body is known as Systemic Lupus Erythematosus (SLE). In a previous study, data were obtained from the results of an analysis based on the Naranjo algorithm obtained were that most respondents fell into the Probable category (Most likely to occur ROM) as many as 14 respondents or 35%, followed by the Definite category (Definite ROM occurs) as many as 12 respondents or 30%. Then the Possible category (Possible ROM occurs) as many as 9 respondents or 22.5% and finally the No ES category as many as 5 respondents or 12.5%. The type of research used was quantitative research with experimental methods through a pretest-posttest control group design by taking a sample and then conducting a pretest first to find out which samples are classified namely interventions experiencing side effects, interventions with no side effects, controls experiencing side effects and controls with no side effects. Based on the results of the Wilcoxon analysis with a p value <0.05, it states that the calendar has an effect on reducing the incidence of side effects in patients. Mann Whitney test showing a p value of 0.000 smaller than 0.05, so it can be interpreted that there are significant differences in side effects in patients with Systemic Lupus Erythematosus (SLE) in the intervention group and control group. The provision of functional calendar media is effective for reducing the incidence of side effects in taking Systemic Lupus Erythematosus (SLE) drugs.